Analisis Pengelolaan Informasi Digital Pelayanan Publik pada PT. XYZ - Zahra Aisha Febrila; Marsofiyati Marsofiyati; Ervina Maulida (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze digital information management and the barriers to the flow of information between work units that affect the achievement of Service Level Agreements (SLAs) at PT. XYZ. This study employed qualitative research methods such as observation, interviews, and documentation. Based on the findings, information management is now digital-based and supported by structured business processes. However, its implementation remains suboptimal due to limited system integration and a lack of coordination among work units. The main barriers identified include delays in information delivery, weak coordination, and low awareness among human resources regarding the importance of timeliness in handling reports. These conditions result in delays in service completion, a backlog of work, and the failure to consistently meet SLA targets. Therefore, optimization efforts are needed through enhancing human resource competencies, strengthening coordination and communication, consistently applying SOPs, and utilizing an automated notification system to improve efficiency and service quality.